Childhood blood pressure, body build, and birthweight: geographical associations with cardiovascular mortality. Issue 4 (August 1992) - Whincup, P H; Cook, D G; Papacosta, O; Walker, M
Abstract : STUDY OBJECTIVE--The aim was to examine whether blood pressure, body build, and birthweight differ between areas of England and Wales with widely differing adult cardiovascular mortality rates. DESIGN--This was a cross sectional survey of children in five towns with exceptionally high and five towns with exceptionally low current adult cardiovascular mortality. SETTING--The study was a school based survey. SUBJECTS--3842 children aged 5.0-7.5 years were selected by stratified random sampling of primary schools (response rate 76%). MEASUREMENTS AND MAIN RESULTS--Blood pressure, pulse rate, height, and weight were measured and birthweight was assessed by maternal recall. Children in towns with high cardiovascular mortality rates were significantly shorter than those in towns with low cardiovascular mortality rates (mean difference 0.9 cm, 95% confidence interval 0.4 to 1.4 cm) and had slightly higher body mass indices (mean difference 0.12 kg/m2, 95% CI -0.03 to 0.27 kg/m2). Mean birthweights were slightly lower in high mortality towns (mean difference 34 g, 95% CI -10 to 78 g), while the proportion of children with low birthweight (< 2500 g) (8.1%) was significantly higher than that in low mortality towns (5.5%) (p = 0.005). Mean differences in blood pressure between high and low mortality towns were small and non-significant, even after adjustment for height. The differences in height between high and low mortality towns were largely independent of social class. However, differences in mean birthweight were markedly reduced once social class was taken into account. CONCLUSIONS--No geographical relationship between childhood blood pressure and adult cardiovascular mortality was detected. Although it is possible that the differences in mean height and body mass index between towns with differing adult cardiovascular mortality may have implications for future patterns of health in these towns, the absence of marked differences in birthweight and blood pressure suggests that hypotheses proposing a direct relationship between intrauterine experience and adult cardiovascular mortality will have limited relevance to geographical variation in cardiovascular disease in this generation.